A 'SMALL TOWN' DISCOVERED TWICE: A FORGOTTEN REPORT OF MAJOR H. H. KITCHENER. (September 2014) - Ben-Yosef, Erez; Levy, Thomas E.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper revisits the contribution of the Palestine Exploration Fund (PEF) to the study of the ancient copper mines of Faynan, Jordan. It reveals that it was a PEF expedition that first reported smelting remains in the northern part of the Faynan region, and demonstrates that the reported remains are the Iron Age site of Khirbat al-Jariya.